An optimization model to select policies for cervical cancer prevention and surveillance in Colombia (2018)
"Analyzing the population dynamics of Cervical Cancer (CC) in Colombia, in order to achieve an efficient selection of policies for the prevention and surveillance of the disease, which must adjust to the budget or governmental restrictions and allow to reduce the prevalence in all its states. A Linear Optimization Model is implemented to serve as support to the decision making of selection of Vaccination and Screening interventions for the prevention of the Human Papilloma Virus and treatment of Neoplastic Lesions and CC."-- Tomado del Formato de Documento de Grado